Assessment of safe child friendly environment of day care centres in government and non government organizations of Dhaka city - Afreen, Fahmida (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2011.